Muscular strength and regional lean mass influence bone mineral health among young females - Guimarães, Bianca Rosa; Pimenta, Luciana Duarte; Massini, Danilo Alexandre [UNESP]; dos Santos, Daniel; Siqueira, Leandro Oliveira da Cruz [UNESP]; Simionato, Astor Reis [UNESP]; dos Santos, Luís Gustavo Almeida [UNESP]; Neiva, Cassiano Merussi [UNESP]; Pessôa Filho, Dalton Muller [UNESP] (FapUNIFESP (SciELO), 2018)
Introduction: Strength training is able to stimulate bone tissue metabolism by increasing mechanical stress on the skeletal system. However, the direct relationship is not yet well established among younger women, since it is necessary to describe which strength enhancement level is able to produce effective changes in bone integrity. Objectives: This study analyzed the influence of muscle strength on bone mineral content (BMC) and bone mineral density (BMD) among female college students. Methods: Fifteen women (24.9 ± 7.2 years) were assessed for regional and whole-body composition by dual-energy X-ray absorptiometry (DXA). The one-repetition maximum (1-RM) tests were assessed on flat bench press (BP), lat pulldown (LPD), leg curl (LC), knee extension (KE), and 45 degree leg press (45LP). Linear regression analyzed the relationships of BMC/BMD with regional composition and 1-RM test values. Measures of dispersion and error (R2adj and SEE) were tested, defining a p-value of 0.05. Results: The mean value of whole-body BMC was 1925.6 ± 240.4 g and the BMD was 1.03 ± 0.07 g/cm2. Lean mass (LM) was related to BMC (R2adj = 0.86, p<0.01, and SEE = 35.6 g) and BMD (R2adj = 0.46, p<0.01, SEE = 0.13 g) in the lower limbs (LL). The 1-RM tests in BP were associated with BMC and BMD (R2adj = 0.52, p<0.01, SEE = 21.4 g, and R2adj = 0.68, p<0.01, SEE = 0.05 g/cm2, respectively) in the upper limbs, while the 1-RM tests in KE were related to BMC and BMD (R2adj = 0.56, p<0.01. SEE = 62.6 g, and R2adj = 0.58, p<0.01, SEE = 0.11 g/cm2, respectively) in the lower limbs. Conclusions: Hence, the 1-RM tests for multi-joint exercises are relevant to the regional BMC/BMD, reinforcing the need to include resistance exercises in training routines with the purpose of improving muscular strength and regional lean mass, thereby ensuring a healthy bone mineral mass. Level of Evidence II; Development of diagnostic criteria in consecutive patients (with applied reference ‘‘gold’’ standard).
Fuerza muscular y masa magra influencian la salud mineral ósea entre jóvenes mujeres
Força muscular e massa magra regional influenciam a saúde mineral óssea entre jovens mulheres
Keywords: Absorptiometry; Body composition; Bone density; Muscle strength; Photon; Young adult